2014
DOI: 10.1007/s00572-014-0580-9
|View full text |Cite
|
Sign up to set email alerts
|

Tuber aestivum association with non-host roots

Abstract: Mycorrhizal fungi provide direct and functional interconnection of soil environment with their host plant roots. Colonization of non-host plants have occasionally been described, but its intensity and functional significance in complex plant communities remain generally unknown. Here, the abundance of ectomycorrhizal fungus Tuber aestivum was measured in the roots of host and non-host (non-ectomycorrhizal) plants in a naturally occurring T. aestivum colony using a quantitative PCR approach. The roots of non-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 19 publications
2
27
1
Order By: Relevance
“…We have made the assumption that these male genotypes have a poor ability to form associations with the host and that they likely survive as free‐living mycelium in the soil or are associated with the roots of non‐ectomycorrhizal plants. It has been demonstrated that roots of herbaceous plants can host truffle mycelium, but the nature of this interaction (such as colonization of the rhizosphere, endophytism,and endomycorrhiza as with orchids) is unknown (Gryndler et al ., ). In our study, we detected the presence of both mating types in 16 out of 20 soil cores.…”
Section: Discussionmentioning
confidence: 97%
“…We have made the assumption that these male genotypes have a poor ability to form associations with the host and that they likely survive as free‐living mycelium in the soil or are associated with the roots of non‐ectomycorrhizal plants. It has been demonstrated that roots of herbaceous plants can host truffle mycelium, but the nature of this interaction (such as colonization of the rhizosphere, endophytism,and endomycorrhiza as with orchids) is unknown (Gryndler et al ., ). In our study, we detected the presence of both mating types in 16 out of 20 soil cores.…”
Section: Discussionmentioning
confidence: 97%
“…However, the colonization of non-host plants by ectomycorrhizal fungi has occasionally been described. Selosse et al (2004) and Gryndler et al (2014) have reported an association between these plants and T. aestivum. While the former detected the fungus in orchid roots, the latter measured its abundance in roots of all plants growing in a brûlé and concluded, from a microscopical inspection of the roots, that T. aestivum is located on the root surface.…”
Section: Discussionmentioning
confidence: 98%
“…() evidenced biotrophic colonization in 17% of species, while three species induced formation of some characteristic features of ectomycorrhizas (see the Commentary by Baldrian & Kohout, ). Truffle species of the ectomycorrhizal genus Tuber (truffles) were shown to also colonize the roots of herbaceous plants where they likely live as endophytes (Gryndler et al ., ; Schneider‐Maunoury et al ., ). Although the latter interaction is still poorly understood, it may account for a specific feature of truffles’ habitat, the brûlé.…”
Section: Do Fungal Ecological Niches Reflect More Than Mycologist's Smentioning
confidence: 99%